(untitled) (Journal of Nepal Geological Society, 2000)
The village of Tatopani lies on a small gravel terrace in the middle reach of the Kali Gandaki River, along a narrow course of about 2 km in length. One kilometre south of the village, a major rockfall occurred recently in the region of the Lesser Himalaya, which is built up of low-grade metamorphic rocks of the Kuncha Group, consisting of a thick sequence of foliated phyllites and bedded quartzites as well as interlayering of both lithologies. The monoclinal structure of these metasedimentary rocks is clearly related to the general trend of the Nepal Himalaya near the Main Central Thrust (MCT): strike NW-SE 140- 150°, dip 25-45° NE. Besides a clear foliation in the phyllites (s1) parallel to the quartzite bedding (s0), four other discontinuities are also developed as steep joints (j1-j4). Two joint sets j1 and j2, both crossing each other and both acting in conjunction with the foliation (s1) as a shear plane, were responsible for the wedge failure of the Tatopani Landslide, which led to a rockfall and avalanche of about 400,000 cubic metres and dammed the river for about 72 hours. It is noteworthy that several other - strikingly similar but older - weathered wedge failure surfaces are exposed at various spots all over the same ridge, which is the spur-ridge dividing the Kali Gandaki River from the Gar Khela tributary. This visible slope instability evidenced by relatively small wedge failures is causally connected with a much larger mechanism, namely mass rock creep or "sagging"- a purely gravitational slope deformation. The repeatedly occurring wedge failures producing landslides (rockfalls and rock avalanches) are caused by extreme shear stress and deep-reaching joints and fissures during mass rock creep. Only the final trigger for landslides or rockfalls is provided by extreme and lengthy monsoon rainstorms, which reinforce the cleft-water pressure inside rock discontinuities and openings, especially along the impermeable interface of quartzites and phyllites (s0 =s1) at the base of the wedge failure. The right (western) bank above the village is morpho-dynamically active also through mass rock creep and “pushes” laterally against the river course. However, the kinematics of the rock slope is rather different because the foliation geometry is more important. The foliation dips obliquely towards the riverside and consequently has facilitated extremely slow large scale dip slope movements along quartzite-phyllite interfaces (s0) without any catastrophic danger. However, the creeping slope movements of thick quartzite: members caused a set of conjugate extension faults producing toppling at the distal slope margins. Rock avalanches from the spur-ridge on the eastern (left) bank of the Kali Gandaki River S of Tatopani will always remain a threat, especially when excessive seasonal rains increase the cleftwater pressure inside the invisibly slow creeping system of the steep bank in an extraordinary manner.